Acute Disseminated Histoplasmosis with Atypical Lymphocytosis in an Immunocompetent Host. (2017) - Elbadawi, Ayman; Ahmed, Hamdy M.A.; Adly, Hussain; Elkhouly, Mohamed A.; Abohamed, Samar; Falsey, Ann R.
Abstract: 65 year-old-male presented with a one-week history of high grade fever, fatigue and confusion which began abruptly two days after a cystoscopy procedure. Past medical history included pulmonary sarcoidosis diagnosed by mediastinal lymph biopsy, diabetes and hypertension. On admission he was febrile and confused with stable vital signs. Initial workup included negative Head CT and lumbar puncture. Blood work revealed normal metabolic and liver function tests with progressive anemia, thrombocytopenia and atypical lymphocytosis of 15–20%. Blood, urine and respiratory cultures all were negative for bacteria and. A bone marrow biopsy was done given the abnormal lymphocytes in peripheral smear, revealing budding yeast consistent with Histoplasma capsulatum . Histoplasma antigen was positive in urine and eventually blood and bone marrow grew H. capsulatum . Patient was started on amphotericin-B for diagnosis of disseminated histoplasmosis. After a 2 week period of amphotericin B, patient was switched to oral Itraconazole to complete 12 months course of treatment.